Nigeria : Publication of Financial Sector Assessment Program Documentation -- Detailed Assessment of Observance of Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2013)
Nigeria undertook a Financial Sector Assessment Program (FSAP), which included a review of the structure of Nigeria's insurance market and the supervisory framework. The assessment was benchmarked against the Insurance Core Principles (ICPs) issued by the International Association of Insurance Supervisors (IAISs). It is advised that the National Insurance Commission (NAICOM) of Nigeria can expand the objective to include the creation of a fair, safe, and stable insurance sector for the benefit and protection of policyholders.